International Cooperation Between Cities Based on the Example of the Cittaslow Network - Farelnik, Eliza; Stanowicka, Agnieszka; Wierzbicka, Wioletta (Olsztyn Economic Journal, 2017)
International cooperation between cities is conducted in numerous spheres, including economic, social, and cultural. It is determined by various factors such as the similarities and previous interrelations between cities, a desire to exchange good practices for management and quality of life improvement and by economic conditions. An example of international cooperation between cities is the Cittaslow network. The aim of this article is to present the concept of international cooperation between cities based on the example of the cities of the Cittaslow network and to identify the determinants and benefits of such cooperation. The Cittaslow network is an affiliation of over 230 cities from all over the world. The reason for their cooperation is the similarities between them, in this case, with respect to their size and the development model they have adopted. Within the Cittaslow network, cooperation takes place between small cities which want to grow in accordance with the “slow” movement principles and make such cooperation very advantageous for the following spheres: environmental, social, economic and spatial.